Unhappy new year: mochi-induced small bowel obstruction - Fujikawa, Hirohisa; Ishimaru, Naoki; Asakawa, Tomohiko; Araki, Makoto (BMJ Case Reports, 2021)
According to previous studies, the incidence of mochi-induced SBO was highest in January (approximately 60%).1 4 5 This seasonal tendency may be unique to the Japanese population. The symptoms of mochi-induced SBO are not specific and are the same as those of usual postoperative adhesive bowel obstruction. [...]history of rice cake consumption and findings of imaging studies are the keys to diagnosis. Small bowel obstruction due to Mochi (rice cake): a case report and review of the literature.